2015
DOI: 10.4103/2230-8210.140226
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum biomarkers for risk assessment in gestational diabetes. A potential universal screening test to predict GDM status

Abstract: The prevalence of gestational diabetes mellitus (GDM) is increasing because of the worldwide obesity/diabetes epidemic. The complications of untreated GDM affect both the mother and baby and include complications during pregnancy as well as increased risk of subsequent type-2 diabetes in mothers and offspring. Standard tests for hyperglycemia in diabetes, such as fasting glucose and hemoglobin (HbA1c), are currently not recommended for GDM screening. Instead, an oral glucose tolerance test is specified, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Traditionally, the risk stratification for GDM in early pregnancy is guided by maternal health characteristics and by previous obstetric outcome parameters [32]. In addition to these conventional risk parameters, several maternal biochemical markers, such as HbA1c, sex hormone binding globulin, and C reactive protein in early pregnancy, are under evaluation as potential predictors of GDM [33,34]. The multivariable logistic regression analysis in our study revealed a linear increase in GDM risk with rising HbA1c-FT levels.…”
Section: Discussionmentioning
confidence: 75%
“…Traditionally, the risk stratification for GDM in early pregnancy is guided by maternal health characteristics and by previous obstetric outcome parameters [32]. In addition to these conventional risk parameters, several maternal biochemical markers, such as HbA1c, sex hormone binding globulin, and C reactive protein in early pregnancy, are under evaluation as potential predictors of GDM [33,34]. The multivariable logistic regression analysis in our study revealed a linear increase in GDM risk with rising HbA1c-FT levels.…”
Section: Discussionmentioning
confidence: 75%
“…non-white ethnicity: including Asian, black Caribbean or Middle Eastern); history of having GDM or a macrosomic infant; maternal obesity[12] and occasionally biochemical markers. [13,14]…”
Section: Introductionmentioning
confidence: 99%
“…Serum and plasma have become the most widely used sample for diabetic biomarker studies212223. Depletion of serum prior to proteomic analysis by immunoaffinity subtraction of specific proteins through the use of targeted polyclonal antibody columns and spin filters has recently emerged as a promising tool for serum prefractionation19.…”
mentioning
confidence: 99%